Elasticity as a biomarker for prostate cancer: a systematic review. (26th July 2013) - Good, Daniel W.; Stewart, Grant D.; Hammer, Steven; Scanlan, Paul; Shu, Wenmiao; Phipps, Simon; Reuben, Robert; McNeill, Alan S.
<x xml:space="preserve">Abstract</x> To systematically review the range of methods available for assessing elasticity in the prostate and to examine its use as a biomarker for prostate cancer. A systematic review of the electronic database PubMed was performed up to December 2012. All relevant studies assessing the use of elasticity as a biomarker for prostate cancer were included except those not studying human prostates or reporting a sensitivity, specificity or quantitative elasticity value. There has been much interest in the use of elasticity in the detection of prostate cancer and there have been many publications using various methods of detection. The most common method of assessment is an imaging method, called sonoelastography. Further imaging methods include ultrasound (US), three‐dimensional US and magnetic resonance elastography. These methods are reviewed for sensitivity and specificity. The other method of assessment is the mechanical method. These use quantitative elasticity values to differentiate benign from malignant areas of the prostate. This method of assessment has shown that the elasticity changes for differing Gleason grades and T stages of disease within the prostate. Quantitative elasticity values offer the potential of using 'threshold' elasticity values under which the prostate is benign. Tissue elasticity has great potential as a diagnostic and prognostic biomarker for prostate cancer and can be assessed using various methods. Currently transrectal sonoelastography has the most evidence supporting its use in clinical practice.